Academia Shrugs: how Addressing Systemic Barriers to Research Efficiency and Quality Teaching Would Allow Criminology to Make a Broader Difference - Stogner, John (American journal of criminal justice, 2022)
Critics have challenged that academics in the fields of criminal justice and criminology inadequately impact society due to their focus drifting from research and teaching practices that make a broader difference. Though the field produces research that sometimes affects policy and often directs students towards successful and fulfilling careers, there is legitimacy to the claim that faculty energies are only partially tied to meaningful difference-making efforts. If criminology fails to successfully focus and, thus, fails to make a difference, all members of the profession bear a degree of responsibility. However, there are numerous structural factors that serve to distract, redirect, and hinder faculty members from successfully serving their students and broader society via their research and teaching. Put simply, "academia shrugs." It fails to adequately reward impactful work while creating obstacles and tasks with no meaningful significance. Using Ayn Rand’s, 1957 novel as a framework, the destruction of motivation in the field is discussed before exploring bureaucracies, practices, and mindsets that weaken the field’s ability to foster success. Specifically, the work identifies administrative bloat, academic redundancies, accreditation dichotomies, overinvestment in faculty governance, biased research, piecemeal publishing, and arcane teaching evaluation practices as contributing to the problem. Broader concerns about the field’s effectiveness are remedied, not by retreating to Galt’s Gulch or engaging in a strike of the mind, but by eliminating these and other similar factors.